Stable carbon, oxygen and clumped isotope data of cultured European land snails - Gábor Újvári; László Rinyu; Anna Sulikowska-Drozd; Barna Páll-Gergely; Stefano M Bernasconi (PANGAEA, 2024)
These data include carbon, oxygen and clumped isotope compositions of shells of three land snail species (Clausilia pumila, Succinella oblonga, Trochulus hispidus) from culturing experiments. During the laboratory experiments at the University of Lodz (Poland) individuals of the three species were kept from October 26, 2021 to June 17, 2022 at 12, 18 and 24 °C temperatures in climate chambers, fed exclusively by fresh lettuce and humidity was controlled using tap water (δ^1?O: -9.29 ±0.52 extperthousand, V-SMOW). δ^1^3C, δ^1?O and Δ?? values of snail shells from lab experiments were determined in two laboratories (Institute for Nuclear Research, Debrecen, and Geological Institute, ETH Zürich) using IRMS. Detailed analysis and interpretations of the results obtained can be read in the original publication.
In: Újvári, G et al. (2024): Meterological and stable carbon, oxygen and clumped isotope data of land snails from Europe [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.969078